Risk of having myocardial infarction in periodontal disease patients: A systematic review - Monika Kumari; Basavaraj Patthi; Chandrasheker Jankiram; Ashish Singla; Ravneet Malhi; Ananthalekshmy Rajeev (Wolters Kluwer Medknow Publications, 2019)
Introduction: Periodontal disease is a common inflammatory disease of the teeth. There is mounting evidence that poor dental health, especially the occurrence of periodontal disease, increases the probability of the occurrence of cardiovascular disease (CVD) which, in turn, is the leading cause of mortality and morbidity throughout the world. Objectives: The study objective was to systematically review the literature and check the risk factors of myocardial infarction (MI) in periodontal disease patients. Materials and Methods: A literature published in PubMed/Medline, PubMed Central, Scopus, Complementary index, Ebscohost, SciELO, Open DOAR, Science Citation Index, and Web of Science was evaluated. Cross-sectional studies assessing the prevalence of periodontal disease among MI patients searched above were included. The methodological quality was assessed using a 10-item ordinal scale for cross-sectional studies. Two authors extracted the information and assessed the methodological quality of the included studies. The search was performed from 1990 till date for all the mentioned databases. There was no lower limit for the analyzed time frame and no language restrictions. The primary outcome measure was the proportion of MI in periodontal disease patients of each study. Results: Out of the total 46 titles appeared, 11 articles fulfilled the criteria and were selected for the review; most of the literature showed an association between MI and periodontal disease. There is a statistically significant increase in MI in periodontal disease patients. CVDs are associated with an increased incidence of periodontal disease, but the association is weak when adjusted with other potential cofounders. The lack of good-quality studies is a major limitation to assess the association between MI and periodontal diseases. Conclusion: Periodontal disease is mostly associated with MI and CVD. The association between periodontal disease and CVD may be confounded by other cofactors such as age, diabetes mellitus, and smoking. However, the association remains weak, and the quality of study is low.